Legal Principles in Antitrust Enforcement - Harold Houba; Evgenia Motchenkova (Tinbergen Institute, 2013)
We study antitrust enforcement that channels price-fixing incentives through setting fines and allocating resources to detection activities. Antitrust fines obey four legal principles: punishments should fit the crime, proportionality, bankruptcy considerations, and minimum fines. Bankruptcy considerations limit maximum fines, ensure abnormal cartel profits and impose a challenge for optimal antitrust enforcement. We integrate the mentioned legal principles into an infinitely-repeated oligopoly model. We derive the optimal level of detection activities and the optimal fine schedule that achieves maximal social welfare under these legal principles. The optimal fine schedule remains below the maximum fine and induces collusion on a lower price by making it more attractive than collusion on higher prices. For a range of low cartel prices, the fine is set to the legal mi nimum. Raising minimum fines will enable the cartel to raise its price and is better avoided. Our analysis and results relate to the marginal deterrence literature.
Keywords: L4; K21; D43; C73; 330; Antitrust enforcement; Antitrust Law; Cartel; Oligopoly; Repeated game